Awareness and Perception of Muslim Consumers on Halal Cosmetics and Personal Care Products - Rahim, Norafni @ Farlina binti; Shafii, Zurina; Shahwan, Syahidawati (International Journal of Business, Economics and Management, 2014)
Muslim populations increasing throughout the world, the awareness on consuming Halal also goes in the same parallel trend. Halal now extends to other areas other than food, such as cosmetics, personal care products, toiletries, fragrance, and skincare products. Malaysia has developed Malaysian Standard MS 2200: Part 1: 2008 as guidelines for Halal cosmetics and personal care industry. Thus, this research paper aims to identify the factors that influence the awareness and perception of Muslim consumers on Halal cosmetics and personal care products. The research also aims to confirm whether the identified variables are significant to the awareness and perception of Muslim consumers on Halal cosmetics and personal care products. The sample of the research consisted of 236 government servants in the state of Selangor. The data are collected through questionnaire and analysed using descriptive analysis and inferential analysis such as correlation and multiple regression analysis. The result of the study revealed that the three factors; Advertising (X1), Knowledge (X2) and Attitude (X3) which all are significant.